Sustainable Vehicle Lifting Solutions: Development and Testing of a Pneumatic Scissor Jack - Mohammad Nor Azami Mohd Rafee; Nurrul Amilin Zainal Abidin; Nurul Hanna Mas’aud; Nur Aini Sabrin Manssor (Journal of Advanced Mechanical Engineering Applications, 2026)
Conventional lifting systems often require manual effort, resulting in inefficient and unstable vehicle lifting operations. An improvised version of lifting system with better efficiency, safety and stability is thus needed to address these problems. Therefore, this study focuses on the design and construction of pneumatic scissor lift jacks, aiming to reduce manual labor and increase vehicle lifting performance. The fabricated prototype is integrated with a double-acting pneumatic cylinder, which was designed using SolidWorks and made of AISI 1020 mild steel. A simulation using Finite Element Analysis shows an approximately 3.52 MPa Von Mises when a 2000 N static load was applied on the lifting platform. Based on the results and data discussion, the stress is lower than the material’s yield, strength, thus confirming that the newly developed lifting system can safely handle the load without permanent deformation. During lifting and lowering process, there were no unusual vibrations and shaking observed, proving that the system demonstrated a stable and functional performance. In brief, it is recommended to utilize rectangular-shaped mild steel structures instead of the current 1 mm thick plates to enhance the lift’s strength and durability. Incorporating an automatic safety lock mechanism when the lift reaches its maximum height extension would be beneficial to prevent accidental lowering and maximize safety for future development.